Genetic Deletion of P2Y2 Receptor Offers Long-Term (5 Months) Protection Against Lithium-Induced Polyuria, Natriuresis, Kaliuresis, and Collecting Duct Remodeling and Cell Proliferation - Zhang, Yue; Riquier-Brison, Anne; Liu, Tao; Huang, Yufeng; Carlson, Noel G.; Peti-Peterdi, János; Kishore, Bellamkonda K. (Frontiers in Physiology, 2018)
Chronic lithium administration for the treatment of bipolar disorder leads to nephrogenic diabetes insipidus (NDI), characterized by polyuria, natriuresis, kaliuresis, and collecting duct remodeling and cell proliferation among other features. Previously, using a 2-week lithium-induced NDI model, we reported that P2Y2 receptor (R) knockout mice are significantly resistant to polyuria, natriuresis, kaliuresis, and decrease in AQP2 protein abundance in the kidney relative to wild type mice. Here we show this protection is long-lasting, and is also associated with significant amelioration of lithium-induced collecting duct remodeling and cell proliferation. Age-matched wild type and knockout mice were fed regular (n = 5/genotype) or lithium-added (40 mmol/kg chow; n = 10/genotype) diet for 5 months and euthanized. Water intake, urine output and osmolality were monitored once in every month. Salt blocks were provided to mice on lithium-diet to prevent sodium loss. At the end of 5 months mice were euthanized and serum and kidney samples were analyzed. There was a steady increase in lithium-induced polyuria, natriuresis and kaliuresis in wild type mice over the 5-month period. Increases in these urinary parameters were very low in lithium-fed knockout mice, resulting in significantly widening differences between the wild type and knockout mice. Terminal AQP2 and NKCC2 protein abundances in the kidney were significantly higher in lithium-fed knockout vs. wild type mice. There were no significant differences in terminal serum lithium or sodium levels between the wild type and knockout mice. Confocal immunofluorescence microscopy revealed that lithium-induced marked remodeling of collecting duct with significantly increased proportion of [H+]-ATPase-positive intercalated cells and decreased proportion of AQP2-positive principal cells in the wild type, but not in knockout mice. Lithium-induced collecting duct cell proliferation (indicated by Ki67 labeling), was significantly lower in knockout vs. wild type mice. This is the first piece of evidence that purinergic signaling is potentially involved in lithium-induced collecting duct remodeling and cell proliferation. Our results demonstrate that genetic deletion of P2Y2-R protects against the key structural and functional alterations in Li-induced NDI, and underscore the potential utility of targeting this receptor for the treatment of NDI in bipolar patients on chronic lithium therapy.